Development of problem-based learning materials on biodiversity using local potential of mangrove forests to enhance critical thinking skills of phase e students - Suparmi, Anik; Paidi, Paidi; Gonzales, Helen Grace B (Directorate of Research and Community ServiceUniversitas Negeri Yogyakarta, 2025)
Students' critical thinking skills in Indonesia remained a concern, as evidenced by suboptimal learning outcomes and low problem-solving abilities. This study aimed to (1) develop the feasibility of learning materials, (2) assess their practicality, and (3) determine their effectiveness in enhancing students' critical thinking skills. This development research produced educational tools, including teaching modules (lesson plans) and student worksheets (LKPD). The study used the 4D technique and took place at SMA Negeri 4 Tarakan with 36 students participating. The results indicated that the learning materials received excellent ratings in content feasibility (81.4%), presentation feasibility (86.5%), language and readability feasibility (89.2%), and graphic feasibility (92.5%). All aspects, including material, language, graphics, and functionality, were classified as highly practical. In the control class, students’ critical thinking skills were classified as moderate (50%), good (11%), very good (13%), and very poor (25%), indicating a concentration within the medium to low range. Meanwhile, the critical thinking skills of the treatment group were categorised as moderate (33%), good (25%), and very good (42%), demonstrating that the developed learning materials were effective in facilitating the Problem-Based Learning (PBL) method to enhance the critical thinking skills of Phase E students at SMAN 4 Tarakan